«Amicus Plato, quia amica veritas» - Pascual LC, Fernando (Alpha Omega, 2010)
This study considers in a contextualized manner the origin of the saying «amicus Plato, sed magis amica veritas», as well as how some authors from the past have taken it. Then it considers in what sense it is legitimate to complement that saying with another one («amicus Plato, quia amica veritas»), and why this complement is important: a good philosophy must honor some thinkers as friends and fellow wayfarers in the search for human wisdom.